Displacement Calculation of a Multi-Stage Homogeneous Loess Slope Under Seismic Action - Jingbang Li; Shuaihua Ye; Xinzhuang Cui; Biao Liu; Nianxiang Li (Buildings)
Slope instability often brings serious threats to human production and life, which causes huge economic losses. The slope displacement calculation under seismic action is very important to ensure the safety and stability of a slope. At present, there are few studies on the displacement calculation of multi-stage loess slopes under seismic action. Based on the basic theory of soil dynamics and the introduction of the comprehensive slope ratio, this paper proposes a new displacement calculating method of multi-stage homogeneous loess slopes under seismic action and provides the calculation formula. The rationality of the theoretical calculation is verified using the numerical simulation software Geo Studio (V2022). The study shows that it is feasible to simplify the geometric characteristics of multi-stage loess slopes by adopting the comprehensive slope ratio, which can also reasonably reflect the displacement characteristics of multi-stage loess slopes under seismic action. The example verification shows that the deviation of the peak horizontal displacement between the calculating method of this paper and the numerical simulation result is 5.5%, which shows that the calculation method of this paper is reasonable and has a certain application value.